2018
DOI: 10.3892/mmr.2018.9020
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑433 reduces cell proliferation and invasion in non‑small cell lung cancer via directly targeting E2F transcription factor 3

Abstract: MicroRNAs (miRNA/miRs) have been associated with the initiation and progression of non‑small‑cell lung cancer (NSCLC). Hence, a comprehensive understanding of the association between dysregulated miRNAs and NSCLC may contribute to the identification of novel therapeutic methods for patients with NSCLC. MiRNA‑433 (miR‑433) has been reported to be dysregulated in numerous types of human cancers; however, its expression pattern, biological roles and associated mechanisms in NSCLC require further investigation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For example, miR-433 inhibits the proliferation and invasion of NSCLC cells by directly targeting E2F3. 10 And miR-182 promotes NSCLC cells by suppressing tumor suppressors FBXW7 and FBXW11. 11 Mounting studies suggest that miR-200a-3p plays a tumor repressive role in multiple tumors, such as liver cancer and esophagus cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-433 inhibits the proliferation and invasion of NSCLC cells by directly targeting E2F3. 10 And miR-182 promotes NSCLC cells by suppressing tumor suppressors FBXW7 and FBXW11. 11 Mounting studies suggest that miR-200a-3p plays a tumor repressive role in multiple tumors, such as liver cancer and esophagus cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutations in BRCC3, which encodes a cell cycle regulator involved in G2/M phase transition, has been linked to myelodysplastic syndrome (MDS), as well as breast and cervical cancers (Boudreau et al 2007;Huang et al 2015;Zhang, Zhou 2018). Mutations in E2F3 have been associated with retinoblastoma, bladder and lung cancer (Ziebold et al 2001;Wang et al 2017a;Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…26 Liu reported that miR-433 inhibit the progression of NSCLC by targeting E2F3. 27 Park indicated that E2F8 is overexpression in LC and is necessary for the growth of LC cells. 28 E2F1 is a transcription factor involved in the regulation of a variety of biological activities, including cell cycle, apoptosis, proliferation, angiogenesis, tumor resistance, infiltration and metastasis.…”
Section: Discussionmentioning
confidence: 99%